UTERUS-SPARING SURGICAL TREATMENT OF SUTURE NECROSIS AFTER CAESAREAN SECTION - CASE SERIES REPORT - Cerović Popović, Radojka; Ćupić, Jovana; Mihaljević, Olga; Pantović, Kosta; Radojević, Miloš (Srpski medicinski časopis Lekarske komore, 2023)
Introduction: Delivery by caesarean section (CS) accounts for approximately 32% of all deliveries worldwide, and it may be associated with early and late complications. Although postpartum uterine suture necrosis is not a common condition, it is associated with high morbidity and mortality in puerperal women, as well as permanent loss of fertility in these patients. In this article, we present seven patients successfully treated conservatively, who were diagnosed with uterine suture necrosis, during puerperium, after caesarean section. Case series report: We present 12 female patients in whom, in the period between February 1, 2019 and November 10, 2022, infection occurred after caesarean section was performed at the Clinic for Gynecology and Obstetrics of the University Clinical Center of Serbia (CGO, UCCS), and clinical suspicion of the presence of uterine suture necrosis arose. Of the total number of patients diagnosed with uterine suture necrosis, seven patients were successfully treated conservatively. Conclusion: The uterus-sparing surgical treatment approach to uterine suture necrosis is a possible alternative to standard treatment, which may allow fertility preservation in patients who have not completed reproduction.